PENGARUH WORK INTERFERING WITH FAMILY, FAMILY INTERFERING WITH WORK DAN ORIENTASI ETIKA TERHADAP TURNOVER INTENTIONS DENGAN JOB SATISFACTION SEBAGAI VARIABEL INTERVENING (Studi Empiris Pada Auditor Kap Jakarta Terdaftar Di Ojk) - -, Sri Yuli Ayu Putri, (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
This research examined the effect of work-family conflict and ethical orientationtowards tunover intentions with job satisfaction as an intervening variable. The population ofthis research are all Public Accounting Firm in Jakarta and is listed in the OJK (Otoritas JasaKeuangan). The sampling method in this research using a convenience sampling. Samplestaken in this research were 150 auditors who have family of 116 Public Accounting Firm listedin the OJK (Otoritas Jasa Keuangan) were taken as samples. The data were analyzed usingStructural Equation Model (SEM) with Smart PLS (Partial Least Squares) program.The results of the research hypothesis Work Interfering with Family (WIF) haspositive effect on Job Satisfaction (JS). While Hypothesis Family Interfering with Work (FIW)has no effect on Job Satisfaction (JS). Besides that hypothesis Work Interfering with Family(WIF) has no effect on Turnover Intentions (TI). Hypothesis Family Interfering with Work(FIW) has no effect on Turnover Intentions (TI). Hypothesis Ethical Orientation (EO) has noeffect on Job Satisfaction (JS). Hypothesis Ethical Orientation (EO) has no effect on TurnoverIntentions (TI). Hypothesis Job Satisfaction (JS) has significant effect on Turnover Intentions(TI). And direct and indirect influence test result proved that the construct of Job Satisfaction(JS) mediated the relationship among Work interfering with Family (WIF), Family interferingwith Work (FIW) and Ethical Orientation (EO) towards Turnover Intentions (TI).Keywords: Work-family conflict, ethical orientation, job satisfaction, turnover intentions,partial least squares (PLS).1. PENDAHULUANKondisi dan perilaku karyawan yang dimiliki perusahaan sangat menentukan kinerja